Bridging the Digital Divide – The Role of the Scientific and Technological Information Stations in Rural Areas of Dong Nai Province - Göransson, Bo; Diep, Doan Dai Ngoc (VNU Journal of Science: Policy and Management Studies, 2016)
Abtract: The result of this study showed that the scientific and technological stations (stations in short) play a pivotal role in rural development and experiences of these stations could be replicated in many other places. These stations have made the considerable achievements in enhancing socio-economic development and functioned as a common platform for the rural areas. These stations have formed a network of the scientific and technological information in rural areas and helped improve the quality of human life. Great achievements from these stations proved their role as “bridging the digital divide” between urban and rural areas in Dong Nai province and they help guarantee the sustainable development in these rural areas ofDongNaiProvince in particular and in the whole country in general Keywords: Information technology and Communications (ICT), ICT4D, digital divide, scientific and technological information station, science and technology, rural development.